Environmental innovation, environmental performance and financial performance: evidence from Malaysian environmental proactive firms - Ong, Tze San; Lee, Ah Suat; Teh, Boon Heng; Magsi, Hussain Bakhsh (MDPI, 2019)
This study is aimed to investigate the relationship between environmental performance, environmental innovation, and financial performance of firms. A total of 124 responses were collected from managers of manufacturers certified by ISO 14001 EMS in Malaysia, and the data was subjected to a structural equation analysis using the Smart PLS version 3.2.7 software. The results have endorsed environmental competitive capabilities i.e. environmental innovation and environmental performance as the key enablers for the creation of economic values for environmental proactive manufacturing firms. Moreover, environmental innovation is also found to be the mediator that transforms the benefits of environmental performance into financial performance.